Public administration: effectiveness and inhibiting factors of one day service - I Wayan Astawa; Gede Wirata; Yudistira adnyana; Sri Sulandari; I Nyoman Suargita (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
"One Day Service" service is a one-day service where each applicant provides documents. This service program aims to provide population and civil registration services in villages, cities and provinces. This service aims to provide convenience to the public in the implementation and public administration. The purpose of this study is to describe and analyze the effectiveness of the "One Day Service" program. The findings of this research report illustrate the effectiveness of population/citizen information services in the program and the obstacles faced by population/citizen information services in the program. This work uses a qualitative descriptive research method. Observations, interviews and documentation are used as data collection techniques. This study shows that the effectiveness of the population registration service in the "One Day Service" program is not yet valid. This is due to the problem of how many have not been answered and processed by the operator due to time constraints and slow network. Sometimes there is a lack of discipline in the assigned tasks and carelessness of the employees managing the service program.